Specific approach to children with behavioural problems - Hutyrová, Miluše (Social Welfare: Interdisciplinary Approach, 2013)
This is a qualitative research study focused on the issue of children with behavioural problems in the Czech Republic. It represents a collection of complete opinions of experts from various professions on the manifestations, causes and possibilities of diagnostic and, in particular, intervention methods in these children. The goal of the study was to defi ne the time-proven approaches, methods and forms of work that could be generalized and recommended as examples of good practise for working with the given target group under the conditions of schools and school consulting facilities